An appraisal of child protection through adoption under Malaysian registration of adoptions Act 1952 and Kafalah in Morocco - Mohd, Azizah; A. Kadir, Nadhilah (Department of Syariah Judiciary Malaysia & Ahmad Ibrahim Kulliyyah of Laws, IIUM, 2021)
This paper deals with the Islamic perspective on child protection for parentless children in Malaysia and Morocco through adoption and kafalah, respectively. As regards adoption in Malaysia, this paper seeks to examine adoption as the means of child protection based on the law and practice of adoption for Muslims in Malaysia, particularly in the Registration of Adoptions Act 1952 (RAA). The paper further investigates the kafalah system in Morocco so as to provide a comparative overview of child protection for parentless children in a Muslim country. Furthermore, the paper examines the significant differences of the legal framework for adoption for Muslims in Malaysia and kafalah system in Morocco. Finally, the paper provides suggestions for improvement of adoption under the RAA as an alternative care option for parentless children in Malaysia. This study also found that family based care, such as adoption, foster care and kafalah is often preferred when deciding a placement for parentless children instead of an institutional setting. The paper adopts a qualitative research primarily based on a library research.